2022
DOI: 10.3847/1538-4357/ac9d2d
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Low-frequency Disturbance Modulation of Magnetosheath Ion Polytropic Index

Abstract: We, using the Cluster data from 2001 to 2010, studied spatial distribution of the ion polytropic index in the magnetosheath, and the modulation of polytropic process by the low-frequency disturbances (4–18 mHz). The total of 30,3283 samples is divided into two sorts: quasi-perpendicular and quasi-parallel propagating ones. The median polytropic index increases with spreads narrowing from the bow shock to the magnetopause. The median polytropic indices are basically between isothermal and adiabatic in the inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The knowledge of its value is of high physical interest and it's been researched for over 50 years (Petrie et al 2007). This research actively continues as observed data of the solar wind from Parker Solar Probe (Nicolaou et al 2023), Ulyssess (Nicolaou et al 2020), Wind (Dayeh & Livadiotis 2022), ACE (Jacobs & Poedts 2011), Cluster (Pang et al 2022) spacecrafts are used to determine the polytropic index. Knowing the nature of the deviations of the polytropic index and the physical processes causing it is a significant step forward in the study of the thermodynamics and energy balance of not only the solar and stellar atmospheric plasma, but also for cold proto-stellar molecular clouds (Donkov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of its value is of high physical interest and it's been researched for over 50 years (Petrie et al 2007). This research actively continues as observed data of the solar wind from Parker Solar Probe (Nicolaou et al 2023), Ulyssess (Nicolaou et al 2020), Wind (Dayeh & Livadiotis 2022), ACE (Jacobs & Poedts 2011), Cluster (Pang et al 2022) spacecrafts are used to determine the polytropic index. Knowing the nature of the deviations of the polytropic index and the physical processes causing it is a significant step forward in the study of the thermodynamics and energy balance of not only the solar and stellar atmospheric plasma, but also for cold proto-stellar molecular clouds (Donkov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of its value is of high physical interest, and it has been researched for over 50 yr (Petrie et al 2007). This research actively continues as observed data of the solar wind from the Parker Solar Probe (Nicolaou et al 2023), Ulyssess (Nicolaou et al 2020), Wind (Dayeh & Livadiotis 2022), ACE (Jacobs & Poedts 2011), and Cluster (Pang et al 2022) spacecraft are used to determine the polytropic index. Knowing the nature of the deviations of the polytropic index and the physical processes causing it is a significant step forward in the study of the thermodynamics and energy balance of not only the solar and stellar atmospheric plasma but also cold protostellar molecular clouds (Donkov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The polytopic index is a fundamental physical parameter for investigating the thermodynamic processes present in space and astrophysical plasma, and the formulation of the theoretical relation between the polytropic index and the anisotropic temperature is currently of considerable recent interest in space plasma (see, e.g., Pang et al 2022;Ghag et al 2024), as the polytropic index has broad applications in the field of space and astrophysical science (see Horedt 2004). For the quasi-static process, Ledoux (1958) describes the relationship between density, temperature, and thermal pressure.…”
Section: Introductionmentioning
confidence: 99%